Strengthening Primary Healthcare in Kosovo Requires Tailoring Primary, Secondary and Tertiary Prevention Interventions and Consideration of Mental Health - Obas, Katrina Ann; Bytyci-Katanolli, Ariana; Kwiatkowski, Marek; Ramadani, Qamile; Fota, Nicu; Jerliu, Naim; Statovci, Shukrije; Gerold, Jana; Zahorka, Manfred; Probst-Hensch, Nicole (Frontiers in Public Health, 2022)
Objectives Kosovo has the lowest life expectancy in the Balkans. Primary healthcare (PHC) plays an essential role in non-communicable disease (NCD) prevention. We described primary, secondary and tertiary prevention indicators in Kosovo and assessed their association with depressive symptoms. Methods PHC users (n = 977) from the Kosovo NCD cohort baseline study were included. Depressive symptoms were assessed using the Depressive Anxiety Stress Scale-21. Cross-sectional associations between depressive symptoms and prevention indicators were quantified with mixed logistic regression models. Results Poor nutrition (85%), physical inactivity (70%), obesity (53%), and smoking (21%) were common NCD risk factors. Many cases of hypertension (19%), diabetes (16%) and Chronic Obstructive Pulmonary Disease (COPD) (45%) remained undetected by a PHC professional. Uncontrolled hypertension (28%), diabetes (79%), and COPD (76%) were also common. Depressive symptoms were positively associated with physical inactivity (OR 1.02; 95% CI 1.00–1.05 per 1-point increase in DASS-21) and undetected COPD (OR 1.07; 95% CI 1.00–1.15), but inversely with undetected diabetes (OR 0.95; 95% CI 0.91–1.00). Conclusions Continued attention and tailored modifications to primary, secondary and tertiary prevention in Kosovo are needed to narrow the Balkan health gap.